2020
DOI: 10.1186/s12884-020-2827-0
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable risk factors of congenital malformations in bale zone hospitals, Southeast Ethiopia: an unmatched case-control study

Abstract: Background: Congenital malformations are structural, functional, and metabolic defects that develop during the organogenesis period and present at birth or later in life. There has been little research on congenital malformations in Ethiopia, knowledge on the incidence of birth defects at birth is unknown and the etiologies of the anomalies are limited. This study, therefore, aimed to assess the modifiable risks of congenital anomalies among women in Bale zone hospitals, Ethiopia. Methods: An unmatched case-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 33 publications
12
40
0
Order By: Relevance
“…In line with the present study, studies done in Iraq and Egypt show that maternal smoking either actual or passive smoking in the first three months of pregnancy was strongly associated with the occurrence of birth defects specifically cleft lip with or without cleft palate [ 14 , 15 ]. Congruent with our findings, a study done in southeastern Ethiopia, Bale zone, Oromia region by Mekonnen et al [ 16 ] reported that maternal exposure to pesticides during early pregnancy had a strong association with the occurrence of CAs with the frequency of 13.2% in exposed compared to 4.2% in unexposed.…”
Section: Discussionsupporting
confidence: 90%
“…In line with the present study, studies done in Iraq and Egypt show that maternal smoking either actual or passive smoking in the first three months of pregnancy was strongly associated with the occurrence of birth defects specifically cleft lip with or without cleft palate [ 14 , 15 ]. Congruent with our findings, a study done in southeastern Ethiopia, Bale zone, Oromia region by Mekonnen et al [ 16 ] reported that maternal exposure to pesticides during early pregnancy had a strong association with the occurrence of CAs with the frequency of 13.2% in exposed compared to 4.2% in unexposed.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the mother who has been exposed to chemicals during the current pregnancy was 4.8 times more prone to have infants with congenital anomalies compared to their corresponding counterparts. Our nding is strongly supported by previous studies carried out by different researchers elsewhere (15,18,(25)(26)(27).…”
Section: Discussionsupporting
confidence: 91%
“…This is in line with the previous studies conducted in Ethiopia (12,15) and California (17). On the other hand, a very recent casecontrol study conducted in Bale Zone, Southeast, Ethiopia indicated that drinking alcohol had hardly any signi cant association with the occurrence of congenital anomalies (18). This might be due to the differences in drinking alcohol cultures.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Despite the aforementioned adverse impacts, national evidence disclosed considerable prevalence of khat [25] and alcohol use [35] during pregnancy in Ethiopia. Furthermore, there are multiple primary studies [28,29,30,35,36,37,38,39,40,41,42,43,44,45,46] showing the delivery of preterm, low birth weight and congenitally malformed neonates among alcohol drinkers, khat chewers, cigarette smokers and narghile users during pregnancy in the country. However, there is no pooled prior evidence regarding the effect of using these substances during pregnancy on birth outcome.…”
Section: Introductionmentioning
confidence: 99%